Shear Wave Velocity Structure Construction Using Ambient Seismic Noise Tomography (ANT) In Palu, Central Sulawesi - Ikhsan, F; Yudistira, Tedi (Jurnal Geofisika, 2019)
Palu is located in Central Sulawesi, Indonesia, characterized by a complex geological setting due to the intersection of Indo-Australia Plate, Philippine Plate, and Eurasia Plate. These plates intersection causes one of the most active fault systems in Indonesia with 42 mm/year relative block motion, the Palu-Koro Fault. Palu-Koro Fault system is a left-lateral fault causing the 7.5 Mw Palu-Donggala Earthquake on 28 September 2018. Moreover, the thickness of the sediment layer in Palu ampli_ed the groud motion. So, it is critical to understand more about the Palu-Koro Fault and its geological system that can be very important for hazard study. In this study, Ambient Seismic Noise Tomography (ANT) was applied to understand the Palu-Koro Fault and its geological system. ANT uses the recorded ambient seismic noise events to obtain experimental Greens function by cross-correlating two seismic record data from two seismic station. Technically, ANT is similar to surface wave tomography which produces two dimensional velocity maps. To produce the two dimensional velocity maps, processing sequence consists of the preparation of single station data, stacking, cross-correlation, Frequency-Time Analysis (FTAN), and surface wave tomography. In this study, the vertical component seismic data was processed from 22 stations in Palu to extract the Rayleigh wave dispersion. The entire data was processed at 0,5 - 5 s period range. In addition, depth inversion step was also applied to get the geological features for the further interpretation. The results of this study are the interstation dispersion curves which indicate the group velocity varies between 0.2 and 2 Km/s, the group velocity maps and the shear wave velocity structure at 0,5 5 Km depth. These results show us the existence of the low-velocity anomaly in the northern part of Palu associated with the coastal sediment, the high-velocity anomaly in the west alongside the N-S direction fault, the low-velocity anomaly in the southern eastern part, and three main geological features in Palu based on the East West cross-section. These results lead to an insight that the heavy damage of the Palu-Donggala Earthquake in 2018 was caused by the thickness of the sediment in Palu.